Tiles, David Sassoon Clocktower - Ghosh, Ayan (2023)
Rustication is used to give visual weight to the ground floor in contrast to smooth ashlar on the floors above. Rustication was used in ancient times but became especially popular in the revived classical styles of Italian Renaissance architecture and that of subsequent periods, particularly on the lower floors of secular buildings.